Ціннісний вимір професійної підготовки майбутнього фахівця - Повар, Ірина; Повар, Олег; Povar, I.; Povar, O. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розкривається сутність аксіологічного підходу до процесу професійної підготовки майбутніх фахівців; визначається зміст поняття формування цінностей і ціннісних орієнтацій у майбутніх фахівців як цілісної системи, розкривається сутність професійно-ціннісного ставлення особистості. The article reveals the essence of the axiological approach to the process of professional training of future specialists. The content of the concept of values as the foundation of social skills and making professional competence of future professionals is determined. The process of the formation of values and value orientations of future professionals as a complete system is analysed, the essence of professionally-valuable relation of the individual is concerned and classification of values related to the profession is given.
Value dimension of vocational training of the future specialist
Keywords: професійна підготовка; professional training; цінність; ціннісні орієнтації; аксіологічний підхід; цілісність формування ціннісних орієнтацій; професійно-ціннісне ставлення; values; value orientations; axiological approach; the integrity of the formation of value orientations; professional-valuable attitude